ANALISIS PENINGKATAN MINAT WISATA MELALUI PENINGKATAN PELAYANAN PADA OBYEK WISATA PANTAI WIDURI KABUPATEN PEMALANG - Mohammad Sigit Taruna (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2012)
The  study,  entitled  "Analysis  of  Tourism Interest  Development  Strategy  through the Service Improvement  at Widuri Coast Pemalang Regency". The aims of this research to  determine  the  optimality  of  service  Widuri  Coast that  can  give  satisfaction  and  to determine the optimal formulation of strategies to improve the quality of service torealize customer  satisfaction.  So  it  really  could  create  interest  for  the  beach  attractiveness  of Widuri  Coast,and  finally  could  increasing  the  original  income  of  Pemalang Regency. Creation of interest in travel by increasing the satisfaction of the tourists / visitors that the number  of  tourists  /  visitors  better,  and  the  tourists  /  visitors  who  have traveled  to  enjoy the scenery  of Widuri  Coast Sights  have  not  lose  to  perform  Sights  tour  back  in  Widuri Coast. Efforts  to  realize  and  enhance  the  satisfaction  of  the  tourists  /  visitors  through optimization service improvements generated by Widuri Coast and Beaches Sights Eating and or other business units in locations Sights Widuri Coast, with an attempt to formulate the  strategy  is  expected  to bring  the  tourist  crowds  pengminatan  Pemalang  particular district  Sights  Beaches  on  Widuri  Coast. This  strategy  is what  should  be  done  by  the managers  of  Widuri  Coast Beaches  Sights  and  managers  Eating  and  or  other  business units who were at the Beaches Sights Widuri Coast.Keyword: travel interests, optimizing service improvements, visitor satisfaction.